Use of Iron Therapy in Chronic Kidney Disease - Jacques Rottembourg; Guy Rostoker (Archives of Clinical Nephrology - Peertechz Publications, 2016)
Anemia is a common complication in patients with chronic kidney disease (CKD), and increases with the progression of renal dysfunction [1]. The main cause of anemia is the inadequate production of erythropoietin (EPO), a glycoprotein mainly produced by the kidney responsible for the growth of erythroid cells in the bone marrow [2]. Iron deficiency is another common cause of anemia in these patients and is a major cause of hyporesponsiveness to erythropoiesis-stimulating agents (ESAs) [3]. Approximately, 50% of patients with CKD, who have anemia and are not receiving ESA or iron supplementation show depleted iron stores in their bone marrow [4]. Although the use of intravenous iron in hemodialysis patients has significantly increased during the last decade [5], the appropriate iron dosing strategy in CKD remains debatable.